Enablers, barriers and challenges: a study of innovation capabilities among SMEs in Singapore - Chen, Matthias (2020)
This research study seeks to understand the drivers, enablers and barriers to innovation among SMEs in Singapore. Over the past several decades, the Singapore government has been instrumental in driving the innovation and growth of the economy. Since the establishment of the Economic Development Board (EDB) to spearhead innovation initiatives and policies in the earlier decades, Singapore’s national innovation system has evolved from being dependent on foreign-MNCs to one which embraced a diversified enterprise ecosystem of both foreign and local enterprises. The Singapore government’s commitment to innovation is further reflected in the amount of investment it has pledged to spur innovation among local firms. Indeed, the recent years have seen an increase in government funding, initiatives and support to build an ecosystem of innovative enterprises. Despite strong governmental support for innovation, studies have shown that SMEs in Singapore were still not proactive in taking steps to innovate and transform their businesses.